2022
DOI: 10.3390/antiox11020309
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Improves Drought Stress Tolerance of Tomato by Modulating Plant Growth, Root Architecture, Photosynthesis, and Antioxidant Defense System

Abstract: Tomato is an important vegetable that is highly sensitive to drought (DR) stress which impairs the development of tomato seedlings. Recently, melatonin (ME) has emerged as a nontoxic, regulatory biomolecule that regulates plant growth and enhances the DR tolerance mechanism in plants. The present study was conducted to examine the defensive role of ME in photosynthesis, root architecture, and the antioxidant enzymes’ activities of tomato seedlings subjected to DR stress. Our results indicated that DR stress st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(99 citation statements)
references
References 64 publications
10
56
1
Order By: Relevance
“…Drought has a negative effect on photosynthesis in wheat ( Ahmad et al, 2018 ). Drought stress can also impair photosynthetic activities of plants, leading to severe growth retardation ( Altaf et al, 2022 ). A study reported that Pn of cotton decreased with the increase in drought intensity ( Deeba et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought has a negative effect on photosynthesis in wheat ( Ahmad et al, 2018 ). Drought stress can also impair photosynthetic activities of plants, leading to severe growth retardation ( Altaf et al, 2022 ). A study reported that Pn of cotton decreased with the increase in drought intensity ( Deeba et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…MT priming enhances ROS scavenging ability, and reduces MDA accumulation ( Altaf et al, 2022 ). The accumulation of MDA is positively correlated with the degree of cell membrane lipid peroxidation, reflecting the degree of damage to the cell membrane ( Imran et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to reestablish the redox homeostasis, melatonin also enhanced the expression of genes encoding antioxidant enzymes (such as APX1 , APX2 , CAT1 , FSD1 , CuZnSOD , and MnSOD ), and improved the activities of APX, SOD, CAT, POD, Δ1-pyrroline-5-carboxylate synthesis (P5CS), as well as the levels of antioxidants (ASC, GSH, proline, and total soluble carbohydrates) [ 12 , 35 , 36 , 40 , 42 , 47 , 54 , 55 , 56 , 57 , 58 , 59 ] ( Table 1 ). Similarly, it was well established that melatonin boosted the activities of many antioxidant enzymes (including SOD, POD, APX, CAT, DHAR, GST, GR, MDHAR, and PPO) and the levels of antioxidants (including ASC, DHA, GSH, proline, flavonoid, carotenoid, and phenolic compounds), thus reducing ROS levels and improving tolerance to drought stress in plants, such as maize, tomato, citrus, soybean, Malus , or kiwifruit plants [ 14 , 39 , 60 , 61 , 62 , 63 , 64 ] ( Table 1 ). Melatonin also acted as a priming agent to improve Medicago sativa tolerance to drought stress via the nitro-oxidative homeostasis [ 65 ].…”
Section: Melatonin Acts As An Antioxidant To Establish Redox Homeosta...mentioning
confidence: 99%
“…Plants can protect themselves from the oxidative stress caused by cold stress by increasing their antioxidant capacity. However, if their antioxidant capacity is weak, applying several exogenous compounds with high-antioxidant properties could help them increase stress tolerance [36]. The use of plant growth regulators and biostimulators such as "melatonin" could be an efficient approach to achieve this objective.…”
Section: Discussionmentioning
confidence: 99%